GROWTH AND DEVELOPMENT OF FEED BEETS DEPENDING ON THE ELEMENTS OF GROWING TECHNOLOGY - Бурко, Леся (SWorldJournal, 2021)
The article presents the results of research on the influence of elements of cultivation technology on the dynamics of leaf formation and crop structure of fodder beet plants. The purpose of the study was to study the peculiarities of growth and developm